2022
DOI: 10.3390/catal12030297
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of TiO2/Hectorite Composite and Its Photocatalytic Degradation of Methylene Blue

Abstract: TiO2/hectorite composite photocatalysts with different molar ratios of lithium, magnesium, and silicon were synthesized by a one-pot hydrothermal method. The samples were characterized by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), N2 adsorption-desorption isotherms, and ultraviolet-visible diffuse reflectance spectra (UV-Vis DRS). When the molar ratio of lithium, mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…33 The weak peaks of 2 θ appear at 32.0°, which may be attributed to the residual starting materials and some intermediate products. 34…”
Section: Resultsmentioning
confidence: 99%
“…33 The weak peaks of 2 θ appear at 32.0°, which may be attributed to the residual starting materials and some intermediate products. 34…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that loading nanoscale photocatalysts onto natural mineral support can inhibit the aggregation, enhance the adsorption capacity and promote photogenerated electron-hole pair separation for hybrid photocatalysts, subsequently improving the dispersion of powdery nanocatalysts and accelerating the degradation rate of organic pollutants [20,21]. Thus, natural minerals have become ideal choices of support materials, such as kaolinite [22], hectorite [23], saponite [24], imogolite [25], and illite [26]. Halloysite nanotubes (HNTs)are silicate mineral [27], which has aluminol (Al-OH) groups on the internal surface and Si-OH on the external surface [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that pure titania exhibited the highest activity in the photocatalytic degradation of Rose Bengal dye under UV light, along with a superior photocurrent response, compared to the incorporated hematite counterparts. Additionally, Yang et al [11] proposed utilizing TiO 2 /hectorite composites with varying molar ratios of lithium, magnesium, and silicon as photocatalysts for the photodegradation of methylene blue (MB) under UV light irradiation. Under optimized conditions (molar ratio of Li/Mg/Si = 1.32/5.34/8), the highest removal rate of MB dye (97.8%) was revealed, while reusability tests after five runs showed only a slight decrease in the photocatalytic activity.…”
mentioning
confidence: 99%